2005
DOI: 10.1074/jbc.m502918200
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin Mediates Desensitization and Internalization but Does Not Affect Dephosphorylation of the Thyrotropin-releasing Hormone Receptor

Abstract: The G protein-coupled thyrotropin-releasing hormone (TRH) receptor is phosphorylated and binds to ␤-arrestin after agonist exposure. To define the importance of receptor phosphorylation and ␤-arrestin binding in desensitization, and to determine whether ␤-arrestin binding and receptor endocytosis are required for receptor dephosphorylation, we expressed TRH receptors in fibroblasts from mice lacking ␤-arrestin-1 and/or ␤-arrestin-2. Apparent affinity for [ 3 H]MeTRH was increased 8-fold in cells expressing ␤-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
32
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 42 publications
9
32
1
Order By: Relevance
“…When GRK2 was overexpressed, TRH-dependent phosphorylation was increased (Fig. 6A), confirming previous evidence that TRH receptor phosphorylation is primarily because of GRKs (14,17,20). Multiple lines of evidence show that the TRH-dependent phosphorylation observed with the coexpression of D71A and 4Ala-TRH receptors is not because of second messenger-activated kinases.…”
Section: Resultssupporting
confidence: 72%
“…When GRK2 was overexpressed, TRH-dependent phosphorylation was increased (Fig. 6A), confirming previous evidence that TRH receptor phosphorylation is primarily because of GRKs (14,17,20). Multiple lines of evidence show that the TRH-dependent phosphorylation observed with the coexpression of D71A and 4Ala-TRH receptors is not because of second messenger-activated kinases.…”
Section: Resultssupporting
confidence: 72%
“…Apparently it does; a recent study (Gardiner et al, 2001) shows that the agonist-phosphorylated G s -coupled D 1 dopamine receptor undergoes the same rate of dephosphorylation whether or not it is able to undergo internalization. Furthermore, a very recent study shows that the agonist-activated G q -coupled thyrotropin-releasing hormone receptor is rapidly dephosphorylated at the cell membrane in mouse embryo fibroblast cells from arrestin-knockout animals where these receptors are unable to undergo significant internalization (Jones & Hinkle, 2005).How to reconcile these recent findings with the earlier results (Yu et al, 1993;Pippig et al, 1995;Krueger et al, 1997)? Iyer et al (2005 suggest that the interpretation of earlier studies on the b 2 -adrenoceptor is made difficult because the 32 P labelling technique reflects a combination of PKA and GRK phosphorylation of the receptor.…”
contrasting
confidence: 47%
“…Apparently it does; a recent study (Gardiner et al, 2001) shows that the agonist-phosphorylated G s -coupled D 1 dopamine receptor undergoes the same rate of dephosphorylation whether or not it is able to undergo internalization. Furthermore, a very recent study shows that the agonist-activated G q -coupled thyrotropin-releasing hormone receptor is rapidly dephosphorylated at the cell membrane in mouse embryo fibroblast cells from arrestin-knockout animals where these receptors are unable to undergo significant internalization (Jones & Hinkle, 2005).…”
mentioning
confidence: 99%
“…Such observations are typical of GPCRs. However, unlike many studies of GPCR desensitization (45)(46)(47), G2A desensitization was not accompanied by obvious loss of the receptor from the cell surface; rather, desensitization to lyso-PL stimulation was temporally associated with visible G2A patching (Fig. 8), perhaps the result of progressive receptor self-association (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…8; lyso-PC stimulation shown). Although receptor internalization has been reported as accompanying desensitization of many GPCRs following stimulation (45)(46)(47), the maintenance of elevated surface G2A through the period of functional desensitization suggested that G2A desensitization in neutrophils is more clearly associated with patching of the receptor than to its internalization. As such, we reasoned that any stimulus mobilizing secretory vesicles and patching G2A would lead to a nonresponsive state to subsequent lyso-PL stimulation.…”
Section: Lyso-pls Enhance Surface Localization and Redistribution Of mentioning
confidence: 99%